2021
DOI: 10.1371/journal.pone.0255120
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and oxidative stress induction by polystyrene nanoparticles in the colorectal cancer cell line HCT116

Abstract: The potential risks of environmental nanoparticles (NPs), in particular Polystyrene Nanoparticles (PNPs), is an emerging problem; specifically, the interaction of PNPs with intestinal cells has not been characterized so far. The mechanism by which polystyrene particles are transferred to humans has not yet been clarified, whether directly through ingestion from contaminated food. We evaluated the interaction between PNPs and colorectal adenocarcinoma cells (HCT116). Cells were exposed to different concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Interestingly, environmental nanoparticles, especially polystyrene nanoparticles, are a potential risk for intestinal injury. It has been reported that PNP exposure can induce cytotoxic and genotoxic effects on cells by inducing oxidative stress related to nuclear damage (Vecchiotti et al, 2021). Homogentisic acid is a metabolite annotated to the styrene degradation pathway, and it has been proven to be cytotoxic for various cell lines (Jurič et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, environmental nanoparticles, especially polystyrene nanoparticles, are a potential risk for intestinal injury. It has been reported that PNP exposure can induce cytotoxic and genotoxic effects on cells by inducing oxidative stress related to nuclear damage (Vecchiotti et al, 2021). Homogentisic acid is a metabolite annotated to the styrene degradation pathway, and it has been proven to be cytotoxic for various cell lines (Jurič et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…of DNA damage, inhibition of apoptosis, promotion of proliferation, differentiation, and migration of malignant cells (Cao et al, 2021;Vecchiotti et al, 2021;Zińczuk et al, 2019). However, little is known about the diagnostic utility of oxidative stress/redox parameters in patients with colorectal cancer (Boakye et al, 2020).…”
Section: The Effects Of Vernonia Cinerea Less Extracts On Antioxidant...mentioning
confidence: 99%
“…Even the ingested MPs and NPs can be uptaken by gut enterocytes, accumulate in villi and release into the bloodstream, and reach other organs and tissues [ 13 ]. Recently the cytotoxic and genotoxic potential of different sizes of PSNPs has been studied in different cell lines and model organisms [ 14 , 15 , 16 , 17 , 18 ]. Due to the distinction in biological processes during differentiation and maturation, different cell lines display a disparity in biological activity against similar exposure [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although our understanding of the effects (such as viability, DNA damage, toxicity, etc.) of MPs and NPs exposure on different human cells is gradually increasing [ 16 , 17 , 20 , 21 , 22 ], there is very little information on the toxic potential of NPs in human lymphocytes [ 18 ]. As the particle sizes decrease to nano-size, its surface-to-volume ratio increases, which makes them biologically more reactive and increases intracellular permeability [ 12 , 17 , 20 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%